Predictors of strut coverage of drug eluting stent implantation in diabetic patients. (1st February 2019) - Briguori, Carlo; Quintavalle, Cristina; Donahue, Michael; D'Alessio, Francesca; D'Amore, Carmen; Signoriello, Giuseppe; del Vecchio, Luigi; De Caterina, Raffaele; Condorelli, Gerolama
Abstract: Background: Incomplete re-endothelialization of drug eluting stent (DES) segments has been associated with the occurrence of major adverse cardiac events after DES implantation. It is unknown whether on-clopidogrel platelet reactivity (OPR) and/or circulating endothelial progenitor cells (EPC) levels may predict uncovered strut rate in diabetic patients treated by DES implantation. Methods: One-hundred and five diabetic patients undergoing elective DES implantation were included into the study. EPC levels and OPR were assessed at 24 h (baseline) and 3 months. EPC were evaluated by flow cytometric analysis and defined by the co-expression of the markers CD34 and KDR. OPR was assessed using the impedance aggregometer. The degree of DES re-endothelialization was assessed at 3 months by optical coherence tomography. Results: A direct correlation was observed between the uncovered strut rate and OPR both at baseline (r = 0.47: p < 0.001) and at the 3 months (r = 0.25: p = 0.015). On the contrary, we found no significant correlation between EPC level and uncovered strut rate either at baseline (r = −0.02; p = 0.85) or at 3 months (r = −0.06; p = 0.13). By multivariable regression analysis, independent predictors of uncovered strut rate > 5% were complex lesions (OR = 5.35; 95% confidence interval 1.32–17.57; p = 0.027) and OPR at baseline (OR = 4.73; 95% confidence interval 1.04–8.14; p = 0.039). Conclusions: In diabetic patients treated with DES implantation OPR at baseline and complex lesions are independent predictors of uncovered strut rate at 3 months. Highlights: We demonstrated for the first time the association between on-treatment platelet reactivity (OPR) and uncovered strut rate. This finding might give insight on the potential mechanism linking OPR to cardiovascular events. Assessment of OPR may help to identify high risk diabetic patients treated by drug eluting stent implantation. Future studies should evaluate whether ticagrelor may reduce the uncovered strut rate and therefore improve outcome.